A attapulgite / molecular sieve composite adsorbent and its preparation method and application
By introducing concave and concave rock stone into the NaX molecular sieve sorbent, and processing of aluminum source crystallization and cation exchange, high-strength and high-crystalline concave and concave rock stone/molecular sieve composite adsorbent is prepared, which solves the insufficient strength of the existing adsorbent and the problem of poor adsorption selectivity significantly improve the adsorption separation effect.
Patent Information
- Application Number
- CN202111681470.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The existing NaX and NaY molecular sieve adsorbents are not strong enough during molding, have low adsorption purification depth, and are limited in product purity and adsorption capacity, resulting in large usage, large device volume, poor adsorption selectivity, easy adsorption olefins, resulting in reduced adsorption efficiency. .
The preparation method of concave and concave rock stone/molecular sieve composite adsorbent is adopted. By grinding the NaX molecular sieve powder with the purified concave and concave rock stone, it is crystallized by adding an aluminum source. After cation exchange and molding activation treatment, it is formed with high strength and high crystallization. Compound adsorbent of degree.
It significantly improves the strength and crystallinity of the adsorbent and improves the adsorption and separation effect, especially in selective adsorption and separation of paraxylene from C8 aromatic isomers, showing broad application prospects.
Smart Images

Figure CN116408044B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite adsorbent preparation, and in particular to an attapulgite / molecular sieve composite adsorbent and a preparation method and application thereof. Background Art
[0002] Adsorbent is the foundation and core of adsorption separation technology, and its active components are mostly zeolite materials. CN1136549A and US6137024 reported adsorbents with Silicalite-1 and hydrogen-type β zeolite as active components, respectively. However, the adsorption capacity of Silicalite-1 and β zeolite is low, which limits their application. European patent EP 0229994 discloses a method for removing dimethyl ether from liquid C3-C5 olefins. The molecular sieve adsorbent has a faujasite structure, including X-type, Y-type molecular sieves and LZ-210 zeolites. The preferred olefin stream is a C4-C5 hydrocarbon stream from fluidized bed catalytic cracking (FCC). The US patent US 4465870 reported the use of NaX and 5A molecular sieves to adsorb and remove methanol, water and methyl tert-butyl ether from C4. The patent CN1806029A applied for by ExxonMobil Chemical Patent Company discloses a method for removing dimethyl ether from olefin streams. The main component of the solid adsorbent used in the invention is a molecular sieve or a metal oxide impregnated with Zn, Mg and other ions. The molecular sieves include small, medium and large pore molecular sieves with a skeleton type of 4-ring to 12-ring or larger. CN1275926A discloses an agglomerated zeolite adsorbent, the active component is an X molecular sieve with an Si / Al atomic ratio of 1 to 1.15, and the binder is a zeolitic clay. After alkali treatment, the clay can be converted into an X molecular sieve to obtain a higher compressive strength and adsorption capacity. CN1565718A uses a small crystal X molecular sieve with a grain size of 0.1 to 0.4 microns as the active component of the adsorbent to improve the mass transfer performance of the adsorbent and improve the adsorption capacity. CN101497022A discloses an agglomerated adsorbent and a preparation method thereof, which adds a pore-forming agent to the mixed powder for preparing the adsorbent, so that a large number of intercrystalline pores with concentrated pore distribution are formed in the adsorbent particles after crystallization, thereby significantly improving the mass transfer performance of the adsorbent.
[0003] Xylene is an important chemical raw material. At present, the industry generally adopts the adsorption separation method to produce high-purity xylene. The adsorption separation technology is composed of molecular sieve adsorbents and simulated moving bed continuous countercurrent separation process, and its core is the development and application of high-efficiency adsorbents. In the adsorption tower, the adsorbent uses different selective adsorption capabilities for mixed xylene isomers. After repeated countercurrent mass transfer exchange, the p-xylene is continuously concentrated, and then the concentrated p-xylene is desorbed by the desorbent, and the desorbent is recovered by distillation extract to obtain high-purity p-xylene. The p-xylene produced by this method has a purity of up to 99.8% and a yield of up to 98%, which has become the main development direction of the p-xylene separation process. The active component of the industrial adsorption separation p-xylene adsorbent is mostly X molecular sieve. The X molecular sieve and clay are mixed evenly in a certain proportion, and the adsorbent beads are obtained after rolling ball molding, drying, roasting and cation exchange. Compressive strength, selectivity, adsorption capacity and mass transfer performance are important indicators for evaluating adsorbents. US4306107 discloses a method for separating meta-xylene and ethylbenzene from mixed C8 aromatics. The method uses NaY zeolite as the active component of the adsorbent and toluene as the desorbent. The method uses the characteristics of NaY zeolite that it has the strongest adsorption capacity for meta-xylene, para-xylene and o-xylene in the middle, and the weakest adsorption capacity for ethylbenzene. The mixed C8 aromatics are passed through a simulated moving bed for countercurrent operation, and meta-xylene, para-xylene, o-xylene and ethylbenzene are obtained at different positions of the simulated moving bed. US4326092 discloses a method for separating meta-xylene from mixed C8 aromatics. The adsorbent is prepared by using NaY zeolite with a silicon oxide to aluminum oxide molar ratio of 4.5 to 5.0, which can obtain a higher selectivity for meta-xylene. US5900523 reported an adsorbent with NaY zeolite having a silicon oxide to aluminum oxide molar ratio of 4.0 to 6.0 as the active component, the water content was controlled to be 1.5 to 2.5% by mass at 500°C, and dihydroindane was used as the desorbent, and liquid phase adsorption separation of meta-xylene was carried out at 100 to 150°C, achieving good separation effect. CN1939883A discloses a method for separating meta-xylene from C8 aromatic isomers, using NaY zeolite having a silicon oxide to aluminum oxide molar ratio of 5 to 6 to prepare the adsorbent, the zeolite containing 0 to 8% water by mass, the adsorption temperature of 25 to 250°C, and the desorbent selected from tetralin and its alkylated derivatives. CN1050595C reported an adsorbent with Y zeolite having a cation position simultaneously occupied by sodium and lithium ions as the active component, and used for liquid phase adsorption separation of meta-xylene from mixed C8 aromatics, achieving higher meta-xylene selectivity. Among them, lithium ions occupy 5% to 35% of the exchangeable sites of the zeolite, and the water content of the adsorbent measured by ignition at 500°C is controlled to be 1.5 to 3.0% by mass. CN102167652A discloses an adsorbent for adsorbing and separating meta-xylene from mixed C8 aromatics, and the active component is cation (sodium and strontium) exchanged Y zeolite, which also achieves good separation effect.
[0004] The active components of the adsorbent for the adsorption separation of p-xylene widely used in industry now are ions of barium, potassium or strontium. X or Y type molecular sieves exchanged alone or as a mixture can effectively selectively adsorb p-xylene from a mixture containing at least one other C8 aromatic isomer. US3558730, US3686342, US3734974, US3626020, US3663638 and CN1137770C disclose some adsorbents containing aluminosilicates exchanged with barium and / or potassium, which can effectively separate p-xylene from a mixture of C8 aromatic isomers. At present, the strength of molecular sieve adsorbent is not ideal when it is molded. In order to meet the requirements of the mechanical properties of the adsorbent in the adsorption separation process, a certain amount of binding agent needs to be added to the adsorbent. US3558732 discloses a system for separating paraxylene from mixed C8 aromatic hydrocarbons by adsorption using toluene as a desorbent. The active component of the adsorbent used is BaKX molecular sieve, which has better adsorption selectivity and product purity than when benzene is used as a desorbent. US20130012377 discloses a paraxylene adsorbent and a preparation method. The method adds a carbohydrate-based molding aid to a NaX type zeolite, and then sprays a mixed alumina sol and a silica sol therein to form mixed particles; the adsorbent is then obtained by drying and calcining, alkali treatment and Ba ion exchange. US3997620 found that compared with BaKX, X molecular sieves were treated with Sr 2+ and Ba 2+After the exchange, although the selectivity of p-xylene / m-xylene (PX / MX) and p-xylene / o-xylene (PX / OX) is reduced, the selectivity of p-xylene / ethylbenzene (PX / EB) and p-xylene / p-diethylbenzene (PX / PDEB) is significantly improved. US6627783 discloses a method for separating p-xylene and ethylbenzene from C8 aromatics by pressure swing adsorption, wherein the active component of the adsorbent is a non-acidic MFI molecular sieve, which can preferentially adsorb p-xylene and ethylbenzene. The research results of Yan [Tsoung Y. Yan. Ind. Eng. Chem. Res., 1989, 28, 572-576.] also show that ZSM-5 molecular sieve has a high adsorption selectivity for p-xylene and ethylbenzene. CN104971695A discloses an adsorbent for pressure swing adsorption separation of C8 aromatic isomers, a preparation method and an application. The active component of the adsorbent is a sodium-type ZSM-5 or MWW molecular sieve. Modification of the molded adsorbent using an organosilicon compound can further improve its adsorption and separation performance. CN03137917 and CN03147981 disclose methods for preparing paraxylene adsorbents, in which a certain amount of kaolin is used in addition to the adsorption active component. CN201710117308 uses X / Silicalite-1 core / shell molecular sieve as the adsorption active component and also uses 2 to 15% by mass of a binder. CN201210273563, under rolling ball molding conditions, mixes the molecular sieve and the binder in a weight ratio of 1:0.02-0.1 on a dry basis and molds the resulting mixture. The addition of the binder will result in the adsorbent having a low crystallinity and poor controllability of the molecular sieve pore size distribution. Theoretically, the adsorption capacity of the adsorbent is proportional to the content of the molecular sieve component therein. The higher the molecular sieve content, the greater the adsorption capacity of the adsorbent. Therefore, reducing the amount of inert binder in the adsorbent and converting it into X molecular sieve as much as possible becomes an effective method to improve the performance of the adsorbent. For example, US 3960774 treats an adsorbent precursor containing X or Y molecular sieve with an aqueous sodium hydroxide solution to increase the crystallinity of the adsorbent, and then performs barium and potassium ion exchange. The method uses extrusion to produce particles with an average particle size of 0.7 mm and a bulk density of about 0.67 g / cm 3. CN 1275926A uses X molecular sieve with low silicon dioxide content and Si / Al atomic ratio of 1-1.5 as raw material to prepare adsorbent, and improves the selectivity of adsorbent by increasing cation exchange sites. CN102497925A discloses a binder-free BaKX molecular sieve adsorbent, which increases the selective part (molecular sieve volume) in the adsorbent by converting the binder into a selective molecular sieve in a conversion process called "molecular sieving". CN109692659A uses molecular sieve and binder to prepare adsorbent, and sodium aluminate and sodium hydroxide are used to in-situ crystallize the binder during the preparation process. CN104477937A introduces a method for preparing adsorbent by mesoporous molecular sieve and binder. CN107073437A uses X-type molecular sieve and binder to prepare adsorbent. The binder-free adsorbent used in CN200980136297 contains the converted part of zeolite X obtained by converting zeolite X precursor. CN201811236632 mixes NaX molecular sieve and clay in a mass ratio of 93-97:3-7, adds an auxiliary agent accounting for 1-5% of the mass of the mixed material and mixes evenly to obtain a mixed powder. The clay used is kaolin, dickite, pearlite or halloysite, forms small balls in a rolling ball device, and after drying, the small balls are soaked in silica sol, and then roasted at 530-700°C to convert the clay into a precursor that can be zeolitized. The fired small balls are placed in an aqueous solution of sodium metaaluminate and sodium hydroxide and mixed evenly to obtain a synthetic system, so that the precursor and the SiO2 in the macroporous channels inside the small balls are in situ crystallized into NaX molecular sieve. USP4818508 discloses a method for synthesizing type A molecular sieve using kaolin with a particle size of 1.5-15μm as a raw material, adding a small amount of porogen, adding water to mix and form, and then roasting at high temperature, hydrothermally treating with alkali solution to convert kaolin into 4A molecular sieve, and adding alumina to supplement aluminum during alkali solution treatment. CN92111878.3 discloses a method for preparing a binder-free 5A adsorbent, wherein 15-35% by weight of kaolin clay and 0.2-2% of sesbania powder are added to the crystals during the synthesis of 4A molecular sieve or after the crystals are washed after synthesis, and then the crystals are molded with sodium cellulose or other starches, and then treated with sodium hydroxide solution and ion exchanged with calcium chloride. CN03115743.2 discloses a method for preparing a 5A molecular sieve that can be used for pressure swing adsorption and petroleum dewaxing, wherein 80-95 parts by weight of 4A molecular sieve raw powder are mixed with 5-20 parts by weight of kaolin clay, 1-50 parts by weight of additive plant fiber are added, and granulation is performed in a high-speed granulator. The granulated intermediate product is then screened, dried and high-temperature roasted according to the product fineness requirements. The roasted intermediate product is treated with alkali in a sodium hydroxide solution, washed and CaCl2 solution is used for CaCl2 reaction. 2+After exchange, washing and drying, the granules are subjected to secondary calcination to obtain a 5A molecular sieve product. CN201110293539.7 discloses a binder-free 5A zeolite adsorbent and a preparation method thereof, wherein NaA type zeolite powder is used as a raw material, and silica sol or sodium silicate is used as a binder to shape the NaA zeolite. After shaping, the zeolite is soaked in an alkaline aqueous solution containing 5% to 35% Al2O3 by weight percentage, so that the binder in the shaped adsorbent is completely converted into a binder-free NaA type zeolite, and then the NaA zeolite is converted into a 5A molecular sieve adsorbent through a calcium exchange step. CN103373891A, CN101045671A and CN108017502A all disclose a method for producing p-xylene and ethylbenzene by adsorption separation from C8 aromatics, comprising separating C8 aromatics by liquid phase adsorption to obtain an extracted oil containing p-xylene and a raffinate containing ethylbenzene, m-xylene and o-xylene. The adsorbent used for liquid phase adsorption separation includes 80-99% by mass of zeolite and 1-20% by mass of a binder. The method uses attapulgite as a binder, but only utilizes the characteristics of attapulgite one-dimensional nanomaterials, and does not convert attapulgite into an effective adsorbent active component. CN1638861A discloses a method for producing a molecular sieve adsorbent blend with improved performance characteristics, including preparing a zeolite powder, preparing a highly dispersed attapulgite fiber binder, mixing the zeolite powder and the highly dispersed attapulgite binder to form a mixture, forming the molecular sieve adsorbent product into a molding material, and calcining the molding material, which has a high diffusion rate and is suitable for thermal swing adsorption and pressure swing adsorption. In the field of adsorption of p-xylene, not only a high diffusion rate is required, but also a high adsorption capacity and adsorption selectivity need to be considered, otherwise p-xylene cannot be efficiently separated from isomers. CN102500315A discloses a LiX molecular sieve adsorbent and a preparation method thereof. First, the X molecular sieve raw powder, binder and auxiliary agent are made into an adsorbent matrix, which is then calcined, boiled in alkali and exchanged with ammonium. Then, the lithium salt solution is impregnated into the molecular sieve adsorbent by an impregnation method, and then dried and calcined to obtain the LiX molecular sieve adsorbent. The binder used is one or more of attapulgite, halloysite, kaolin, tert-butyl clay, bentonite or sheep liver clay. The auxiliary agent is one or more of tianqing powder, cellulose, starch or silica-alumina sol. The alkaline solution is NaOH, KOH or a mixed solution thereof. Ammonium salts include one or more of ammonium sulfate / ammonium bisulfate, ammonium nitrate, ammonium chloride, ammonium carbonate, ammonium salts of organic acids, etc. This method increases the content of X molecular sieve in the adsorbent and also increases Li by calcination, alkali boiling and ammonium exchange. + The same problem of this method is that adding a binder only increases the strength of the adsorbent, but fails to effectively convert the binder into an adsorption active component, and the effective adsorption capacity is not improved.
[0005] Although the above patent reports use barium, potassium or strontium ions alone or as a mixture to exchange ions on X or Y type molecular sieves to obtain adsorbents for separating paraxylene, the introduction of the binder makes it difficult to balance the crystallinity of the molecular sieve and the strength of the adsorbent. Although the eight-sided zeolite molecular sieves NaX and NaY have strong polarity, especially the removal of polar impurities with high removal efficiency, they are often used for adsorption and purification of liquid raw materials. However, the existing NaX and NaY molecular sieve adsorbents have low adsorption and purification depths on the one hand, and the product purity cannot meet the downstream production requirements. At the same time, the adsorption capacity is limited, which makes the amount of adsorbent and the purification device bulky, increases the investment cost of the device, and frequent regeneration also complicates the operation. On the other hand, the adsorption selectivity is poor, and a large amount of olefins are also adsorbed while adsorbing oxygen-containing compounds, and the release of more heat during olefin adsorption has an adverse effect on the adsorption efficiency. In addition, the olefins remaining in the adsorbent pores during the regeneration process are prone to carbonization at high temperatures, which reduces the performance of the adsorbent. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a attapulgite / molecular sieve composite adsorbent. The composite adsorbent obtained by the preparation method has significantly improved strength and crystallinity, and can significantly improve the adsorption and separation effect.
[0007] To this end, the present invention provides a method for preparing a attapulgite / molecular sieve composite adsorbent, comprising the following steps:
[0008] (1) Using NaX molecular sieve powder as a raw material, adding purified attapulgite, grinding, adding an aluminum source for crystallization, filtering, washing, and drying to obtain an attapulgite / molecular sieve composite adsorbent precursor;
[0009] (2) The composite adsorbent precursor obtained in step (1) is subjected to metal cation exchange, and then filtered, washed, dried, molded, and activated to obtain the composite adsorbent.
[0010] Specifically, after the molecular sieve is loaded with purified attapulgite and an aluminum source is added for crystallization, the strength of the obtained composite adsorbent is significantly improved, the crystallinity is significantly improved, and the pore size distribution of the adsorbent is regulated by cation exchange, which can significantly improve the adsorption and separation effect.
[0011] The method for preparing the attapulgite / molecular sieve composite adsorbent of the present invention, wherein preferably, the purified attapulgite refers to the attapulgite obtained by dispersing and beating and removing impurities; the addition amount of the purified attapulgite is 1% to 10% of the mass of the NaX molecular sieve powder.
[0012] The preparation method of the attapulgite / molecular sieve composite adsorbent described in the present invention is preferably that the soluble salt in the soluble salt solution used for metal cation exchange is a potassium salt and / or a barium salt, and is further preferably one or more of KCl, K2SO4, K2CO3, KNO3, BaCl2 and Ba(NO3)2.
[0013] The preparation method of the attapulgite / molecular sieve composite adsorbent of the present invention is not limited to the grinding method, which can be adjusted according to the properties of the raw materials. Preferably, the grinding is dry ball milling. When the dry ball milling is adopted, the ball-to-material ratio is 2:1-15:1, the ball milling speed is 300-1000 r / min, and the grinding time is 0.5-24 hours. The dry ball milling is to add attapulgite into the ball mill for ball milling.
[0014] The preparation method of the attapulgite / molecular sieve composite adsorbent of the present invention, wherein preferably, the adding of aluminum source for crystallization comprises the following steps: stirring at 40°C to 60°C, heating to 90°C to 100°C for crystallization for 6 to 12 hours.
[0015] The preparation method of the attapulgite / molecular sieve composite adsorbent of the present invention, wherein preferably, the metal cation exchange comprises the following steps: the composite adsorbent precursor obtained in step (1) is impregnated with a metal cation-containing solution, the impregnation temperature is 30°C to 100°C, more preferably 40°C to 90°C, the impregnation time is 2 to 28 hours, more preferably 6 to 24 hours. The present invention does not limit the metal cation exchange method, and multiple equal volume impregnations are recommended. For example: potassium salt and barium salt are impregnated and dried multiple times in equal volumes, respectively.
[0016] The preparation method of the attapulgite / molecular sieve composite adsorbent of the present invention, wherein preferably, in step (1), washing is performed until the pH value is 7-8; in step (2), the drying conditions are: temperature 90°C-180°C, more preferably 100°C-160°C, time 1-15h, more preferably 2-12h; the activation conditions are: temperature 100°C-350°C, more preferably 150°C-300°C, time 1-7h, more preferably 2-6h.
[0017] The method for preparing the attapulgite / molecular sieve composite adsorbent of the present invention is preferably that the aluminum source is selected from at least one of sodium aluminate, aluminum sol, and water glass; further preferably, the aluminum source is added in an amount of 1% to 10% of the mass of the NaX molecular sieve powder, and more preferably 3% to 8%.
[0018] To this end, the present invention also provides a attapulgite / molecular sieve composite adsorbent prepared by the above preparation method, wherein the cation content in the composite adsorbent is 5% to 40% by mass of the oxide, and further preferably, the composite adsorbent is 20-40 mesh.
[0019] To this end, the present invention also provides an application of the above-mentioned attapulgite / molecular sieve composite adsorbent for adsorbing and separating p-xylene in mixed xylene. Further preferably, when the composite adsorbent is adsorbing and separating p-xylene, the temperature is 150-200°C, further preferably 170-180°C, the pressure is 0.7-0.9MPa, the composite adsorbent filling amount is 10-30mL, the total filling amount of quartz sand is 40-20mL, and the feed rate is 0.1-0.5mL / min.
[0020] Specifically, the method for preparing the attapulgite / molecular sieve composite adsorbent provided by the present invention comprises the following steps:
[0021] (1) Preparation of attapulgite / molecular sieve composite adsorption precursor: weigh NaX molecular sieve powder, add purified attapulgite at a mass percentage of 1% to 10%, grind under the conditions of ball-to-material ratio of 2:1 to 15:1, ball mill speed of 300 to 1000 r / min, and grinding time of 0.5 to 24 hours; add the ball-milled powder to an aluminum source, stir at a temperature of 40°C to 60°C, and heat to 90°C to 100°C for crystallization for 6 to 12 hours; filter, wash to a pH of 7 to 8, and dry to obtain a attapulgite / molecular sieve composite adsorption precursor;
[0022] (2) Preparation of attapulgite / molecular sieve composite adsorbent: The precursor is impregnated with a metal cation-containing solution at a temperature of 30°C to 100°C, preferably 40°C to 90°C, for 2 to 28 hours, preferably 6 to 24 hours. The adsorbent powder is obtained by filtering, washing, drying, molding, activating, and crushing.
[0023] The advantages of the present invention are mainly reflected in the following aspects:
[0024] (1) The composite adsorbent has a simple preparation method, large adsorption capacity, good selectivity, and can effectively adsorb and separate liquid mixtures. It has broad application prospects in the selective adsorption and separation of p-xylene from C8 aromatic isomers.
[0025] (2) The strength of the composite adsorbent formed after adding attapulgite is increased, which effectively reduces the use of binders and avoids the reduction of adsorbent crystallinity and changes in adsorbent structure and performance caused by the use of binders.
[0026] (3) The requirements for the raw material NaX molecular sieve are relatively low, and the raw material source is wide and cheap; adding purified attapulgite ball milling can greatly improve the strength of the composite adsorbent; adding aluminum source crystallization can significantly improve the crystallinity of the composite molecular sieve; cation exchange of the precursor can effectively load the active components and regulate the pore structure, thereby improving the adsorption capacity and adsorption selectivity of the composite molecular sieve. In addition, the problem of ensuring high crystallinity and high strength at the same time has been solved.
[0027] (4) Attapulgite clay is abundant in my country and is a natural one-dimensional nanomaterial with excellent performance and low price. It is an ideal raw material for crystallization. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart of the preparation of the attapulgite / molecular sieve composite adsorbent;
[0029] Figure 2 This is a diagram of an evaluation device for the adsorption and separation of p-xylene by the attapulgite / molecular sieve composite adsorbent of the present invention;
[0030] Figure 3 It is a structural schematic diagram of a fixed bed of the present invention;
[0031] Reference numerals:
[0032] 1,7—stainless steel wire mesh;
[0033] 2,5—quartz sand;
[0034] 3—Insulation layer;
[0035] 4—Adsorbent;
[0036] 6—Fixed bed filling tube.
[0037] 8—Raw material tank;
[0038] 9—Electronic balance;
[0039] 10—metering pump;
[0040] 11—Fixed bed reactor;
[0041] 12—sampling valve;
[0042] 13—Sampling bottle;
[0043] 14—Back pressure valve;
[0044] 15—collection tank;
[0045] 16—sampling valve 2;
[0046] 17—Nitrogen valve;
[0047] 18—Nitrogen cylinder. DETAILED DESCRIPTION
[0048] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0049] See also Figure 1 As shown, the preparation method of the attapulgite / molecular sieve composite adsorbent provided by the present invention comprises the following steps:
[0050] (1) Preparation of attapulgite / molecular sieve composite adsorption precursor: weigh NaX molecular sieve powder, add purified attapulgite at a mass percentage of 1% to 10%, and dry ball mill at a ball-to-material ratio of 2:1 to 15:1, a ball mill speed of 300 to 1000 r / min, and a grinding time of 0.5 to 24 hours; add an aluminum source to the mixed powder after ball milling, stir at a temperature of 40°C to 60°C, and heat to 90°C to 100°C for crystallization for 6 to 12 hours; filter, wash to a pH of 7 to 8, and dry to obtain a attapulgite / molecular sieve composite adsorbent precursor;
[0051] (2) Preparation of attapulgite / molecular sieve composite adsorbent: The composite adsorbent precursor is impregnated with a metal cation-containing solution at a temperature of 30°C to 100°C, preferably 40°C to 90°C, for 2 to 28 hours, preferably 6 to 24 hours. The exchange product obtained is filtered, washed, dried, formed, activated, and crushed to obtain an adsorbent powder.
[0052] See also Figure 2 As shown, Figure 2 This is a diagram of an evaluation device for adsorption and separation of paraxylene by attapulgite / molecular sieve composite adsorbent. The evaluation device includes: an electronic balance 9, a raw material tank 8, a metering pump 10, a fixed bed reactor 11, a sampling bottle 13, a collecting tank 15 and a nitrogen cylinder 18. A sampling valve 12 is installed on the sampling bottle 13, a back pressure valve 14 is installed on the pipeline between the sampling bottle 13 and the collecting tank 15, a sampling valve 2 16 is installed on the outlet pipeline of the collecting tank 15, and a nitrogen valve 17 is installed on the nitrogen cylinder 18. Among them, an electric heating coupler is installed in the middle of the heating tube of the fixed bed reactor 11 to measure the temperature. The outer layer is covered with an insulation layer, which is conducive to maintaining a constant temperature state in the heating tube. A composite adsorbent is installed in the middle of the heating tube, and quartz sand is respectively loaded into the upper and lower parts of the composite adsorbent. The composite adsorbent and quartz sand are filled. See FIG. Figure 3 . See Figure 3As shown, the two ends of the heating tube, i.e., the fixed bed filling tube 6, are provided with stainless steel wire meshes 1 and 7, and quartz sand 2, composite adsorbent 4, and quartz sand 5 are filled between the stainless steel wire meshes 1 and 7 from top to bottom. The outer wall of the fixed bed filling tube 6 is wrapped with a heat preservation layer 3. The C8 aromatic hydrocarbon isomer raw material liquid is configured according to a certain ratio, and the raw material liquid is input into the fixed bed reactor 11 by a metering pump under certain temperature and pressure conditions. The feed amount and feed time are metered, and a sample is taken every 5 minutes when liquid flows out of the sampling valve 12, and 10 samples are collected continuously. The composition of the raw materials and products is analyzed by chromatography, and the adsorption capacity of the unit mass of the adsorbent can be calculated by subtracting the total amount of feed from the total amount of discharge.
[0053] Example 1 KCl-exchanged catalyst
[0054] first step:
[0055] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 10g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven and dry at 110°C for 6 hours, and calcine at 500°C for 2 hours to obtain a attapulgite / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 0.8g / ml.
[0056] Step 2:
[0057] Weigh 5.72g KCl and dissolve it in 37.5ml water to prepare a KCl solution for use. Weigh 30g of attapulgite / molecular sieve composite adsorbent precursor, ion exchange the KCl solution at 90°C with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and dry in an oven at 110°C for 6 hours to obtain a KCl solution attapulgite / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain a KCl attapulgite / molecular sieve composite adsorbent that has been ion exchanged three times.
[0058] Step 3:
[0059] 20g of attapulgite / molecular sieve composite adsorbent exchanged 3 times with KCl was pressed into tablets and crushed, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.7MPa and the temperature was raised to 170°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0060] Example 2 BaCl2-Exchanged Catalyst
[0061] first step:
[0062] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 10g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven and dry at 110°C for 6 hours, and then calcine at 500°C for 2 hours to obtain an attapulgite / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 0.9g / ml.
[0063] Step 2:
[0064] Weigh 4.55g BaCl2 and dissolve it in 33.4ml water to prepare BaCl2 solution for use. Weigh 30g attapulgite / molecular sieve composite adsorption precursor, use BaCl2 solution at 90℃ with a solid-liquid ratio of 1:1 for ion exchange for 12 hours, filter, wash, and put it in an oven at 110℃ for 6 hours to obtain BaCl2 attapulgite / molecular sieve composite adsorbent with ion exchange once. Repeat the above steps twice to obtain BaCl2 attapulgite / molecular sieve composite adsorbent with ion exchange 3 times.
[0065] Step 3:
[0066] 20g of the attapulgite / molecular sieve composite adsorbent exchanged 3 times by BaCl2 was crushed into tablets, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0067] Example 3 KCl and BaCl2 co-exchanged catalyst
[0068] first step:
[0069] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 10g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, control the temperature to stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven and dry at 110°C for 6 hours, and then calcine at 500°C for 2 hours to obtain the attapulgite / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 0.8g / ml.
[0070] Step 2:
[0071] Weigh 2.86g KCl and 2.27g BaCl2 and dissolve them in 37.5ml water to prepare a mixed solution for use. Weigh 30g of attapulgite / molecular sieve composite adsorption precursor, use the mixed solution to perform ion exchange at 90°C with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and put it in an oven to dry at 110°C for 6 hours to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged three times.
[0072] Step 3:
[0073] 20g of the attapulgite / molecular sieve composite adsorbent exchanged 3 times with K and Ba was crushed into tablets, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0074] Example 4 KCl and BaCl2 co-exchanged catalyst, changing the amount of sodium aluminate
[0075] first step:
[0076] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 13g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven and dry at 110°C for 6 hours, and then calcine at 500°C for 2 hours to obtain an attapulgite / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 1g / ml.
[0077] Step 2:
[0078] Weigh 2.86g KCl and 2.27g BaCl2 and dissolve them in 30ml water to prepare a mixed solution for use. Weigh 30g of attapulgite / molecular sieve composite adsorption precursor, use the mixed solution to perform ion exchange at 90°C with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and put it in an oven to dry at 110°C for 6 hours to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged three times.
[0079] Step 3:
[0080] 20g of the attapulgite / molecular sieve composite adsorbent exchanged 3 times with K and Ba was crushed into tablets, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0081] Example 5 KCl and BaCl2 co-exchanged catalyst, changing the cation ratio
[0082] first step:
[0083] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 10g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, control the temperature to stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven to dry at 110°C for 6 hours, and then calcine at 500°C for 2 hours to obtain an attapulgite / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 1g / ml.
[0084] Step 2:
[0085] Weigh 5.72g KCl and 4.55g BaCl2 and dissolve them in 30ml water to prepare a mixed solution for use. Weigh 30g of attapulgite / molecular sieve composite adsorption precursor, use the mixed solution to perform ion exchange at 90°C with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and put it in an oven to dry at 110°C for 6 hours to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged three times.
[0086] Step 3:
[0087] 20g of the attapulgite / molecular sieve composite adsorbent exchanged 3 times with K and Ba was crushed into tablets, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0088] Comparative Example 1 Preparation of Kaolin / Molecular Sieve Composite Adsorbent
[0089] first step:
[0090] Weigh 150g NaX molecular sieve powder, add 5g kaolin, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min. Dissolve 10g sodium aluminate in water, stir at room temperature for 30 minutes, add the ball-milled powder to the sodium aluminate solution, control the temperature to stir at 40°C, then heat to 90°C for crystallization for 12 hours, filter, wash to a pH of 7-8, put in an oven and dry at 110°C for 6 hours, and then calcine at 500°C for 2 hours to obtain a kaolin / molecular sieve composite adsorbent precursor. The precursor bulk ratio was measured to be 0.8g / ml.
[0091] Step 2:
[0092] Weigh 2.86g KCl and 2.27g BaCl2 and dissolve them in 37.5ml water to prepare a mixed solution for use. Weigh 30g kaolin / molecular sieve composite adsorption precursor, use the mixed solution to perform ion exchange at 90℃ with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and dry in an oven at 110℃ for 6 hours to obtain a kaolin / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain a kaolin / molecular sieve composite adsorbent that has been ion exchanged three times.
[0093] Step 3:
[0094] 20g of kaolin / molecular sieve composite adsorbent exchanged 3 times with K and Ba was crushed into tablets and sieved with 20 mesh for later use. 20mL of quartz sand, 10mL of 20 mesh kaolin / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0095] Comparative Example 2 Preparation of non-secondary crystallized attapulgite / molecular sieve composite adsorbent
[0096] first step:
[0097] Weigh 150g NaX molecular sieve powder, add 5g purified attapulgite, grind for 12 hours at a ball-to-material ratio of 5:1 and a ball mill speed of 1000r / min, and calcine at 500℃ for 2 hours to obtain an attapulgite / molecular sieve composite adsorbent precursor. The bulk ratio of the adsorbent precursor was measured to be 1g / ml.
[0098] Step 2:
[0099] Weigh 2.86g KCl and 2.27g BaCl2 and dissolve them in 30ml water to prepare a mixed solution for use. Weigh 30g of attapulgite / molecular sieve composite adsorption precursor, use the mixed solution to perform ion exchange at 90°C with a solid-liquid ratio of 1:1 for 12 hours, filter, wash, and put it in an oven to dry at 110°C for 6 hours to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged once. Repeat the above steps twice to obtain an attapulgite / molecular sieve composite adsorbent that has been ion exchanged three times.
[0100] Step 3:
[0101] 20g of the attapulgite / molecular sieve composite adsorbent exchanged 3 times with K and Ba was crushed into tablets, and 20 meshes were sieved for standby use. 20mL of quartz sand, 10mL of 20 mesh attapulgite / molecular sieve composite adsorbent and 20mL of quartz sand were sequentially loaded into the fixed bed, the pressure was maintained at 0.87MPa and the temperature was raised to 180°C for activation for 1 hour, and the raw material liquid with a ratio of ethylbenzene: o-xylene: p-xylene: m-xylene = 1 / 1 / 2 / 3 (molar ratio) was fed with a metering pump, the feed flow rate was 0.1mL / min, the feed amount and feed time were metered, and samples were taken every 5 minutes when liquid flowed out of the sampling valve, and 10 samples were collected continuously. After the sampling was completed, the feeding was stopped, the pressure was maintained and the temperature was lowered, and the composition of each sample was analyzed by gas chromatography.
[0102] Table 1 Physical properties and adsorption performance of composite adsorbent
[0103] Serial number p-Xylene adsorption capacity mg / g Strength N Example 1 109 87 Example 2 122 90 Example 3 140 91 Example 4 135 89 Example 5 142 92 Comparative Example 1 73 79 Comparative Example 2 66 81
[0104] It can be seen from Table 1 that the strength, adsorption performance and adsorption selectivity of the composite adsorbent prepared in Examples 1-5 are significantly better than those in Comparative Examples 1-2.
[0105] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.
Claims
1. An application of an attapulgite / molecular sieve composite adsorbent for adsorbing and separating p-xylene from mixed xylene, characterized in that: When the composite adsorbent is used for adsorption and separation of p-xylene, the temperature is 150-200°C, the pressure is 0.7-0.9 MPa, the loading amount of the composite adsorbent is 10-30 mL, the total loading amount of quartz sand is 40-20 mL, and the feed rate of the raw material is 0.1-0.5 mL / min; The preparation method of the attapulgite / molecular sieve composite adsorbent comprises the following steps: (1) Using NaX molecular sieve powder as raw material, adding purified attapulgite, grinding, adding aluminum source for crystallization, filtering, washing, and drying to obtain an attapulgite / molecular sieve composite adsorbent precursor; (2) exchanging the composite adsorbent precursor obtained in step (1) with metal cations, and then filtering, washing, drying, molding, and activating to obtain the composite adsorbent; The soluble salts in the soluble salt solution used for the metal cation exchange are potassium salts and barium salts; The amount of the purified attapulgite added is 1% to 10% of the mass of the NaX molecular sieve powder; The adding of aluminum source for crystallization comprises the following steps: stirring at a temperature of 40°C to 60°C, heating to 90°C to 100°C for crystallization for 6 to 12 hours; The amount of aluminum source added is 1% to 10% of the mass of the NaX molecular sieve powder; The cation content in the composite adsorbent is 5% to 40% by weight of oxide.
2. The use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene in mixed xylene, characterized in that: The purified attapulgite refers to the attapulgite obtained by dispersing and beating and removing impurities.
3. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene in mixed xylene, characterized in that: The potassium salt is one or more of KCl, K2SO4, K2CO3, and KNO3; the barium salt is one or more of BaCl2 and Ba(NO3)2.
4. The use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene in mixed xylene, characterized in that: The grinding is dry ball milling. When the dry ball milling is adopted, the ball-to-material ratio is 2:1-15:1, the ball milling speed is 300-1000 r / min, and the grinding time is 0.5-24 hours.
5. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene from mixed xylene, characterized in that: The metal cation exchange comprises the following steps: impregnating the composite adsorbent precursor obtained in step (1) with a metal cation-containing solution at a temperature of 30° C. to 100° C. for a time of 2 to 28 hours.
6. Use of the attapulgite / molecular sieve composite adsorbent according to claim 5 for adsorbing and separating p-xylene from mixed xylene, characterized in that: The immersion temperature is 40°C to 90°C, and the immersion time is 6 to 24 hours.
7. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene from mixed xylene, characterized in that: In step (1), washing is performed until the pH value is 7 to 8; in step (2), the drying conditions are: temperature 90°C to 180°C, time 1 to 15 hours; the activation conditions are: temperature 100°C to 350°C, time 1 to 7 hours.
8. Use of the attapulgite / molecular sieve composite adsorbent according to claim 7 for adsorbing and separating p-xylene from mixed xylene, characterized in that: In step (2), the drying conditions are: temperature 100°C to 160°C, time 2 to 12 hours; the activation conditions are: temperature 150°C to 300°C, time 2 to 6 hours.
9. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene from mixed xylene, characterized in that: The aluminum source is selected from at least one of sodium aluminate and aluminum sol; the amount of the aluminum source added is 3% to 8% of the mass of the NaX molecular sieve powder.
10. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene from mixed xylene, characterized in that: The composite adsorbent has a mesh size of 20-40.
11. Use of the attapulgite / molecular sieve composite adsorbent according to claim 1 for adsorbing and separating p-xylene from mixed xylene, characterized in that: When the composite adsorbent is used for adsorption and separation of p-xylene, the temperature is 170-180°C.
Citation Information
Patent Citations
Method for adsorbing-crystal separation of paraxylene and ethylbenzene from C8 aromatic
CN101045671A
Coalescence type zeolite sorbent and preparation method thereof
CN101497022A
Binderless adsorbents with improved mass transfer properties and their use in adsorptive separation of para-xylene
CN102159674A
Adsorbent for adsorbing and separating m-xylene and preparation method of same
CN102167652A
Binderless zeolitic adsorbents, methods for producing binderless zeolitic adsorbents, and processes for adsorptive separation of para-xylene from mixed xylenes using the binderless zeolitic adsorbents
CN102497925A
Cited By
EMT / FAU composite molecular sieve and preparation method and application thereof
CN122321791A
EMT / FAU composite molecular sieve, preparation method therefor and use thereof
CN122321791B